2017
DOI: 10.1016/j.celrep.2016.12.030
|View full text |Cite
|
Sign up to set email alerts
|

IMPDH2 Is an Intracellular Target of the Cyclophilin A and Sanglifehrin A Complex

Abstract: Natural products have demonstrated utility in the clinic and can also act as probes to understand complex cellular pathways. Sanglifehrin A (SFA) is a mixed polyketide and non-ribosomal peptide synthase natural product with sub-nano-molar affinity for its receptor cyclophilin A (PPIA). It has been shown to behave in vitro as an immune suppressant. Here, we identify inosine-5'-monophosphate dehydrogenase 2 (IMPDH2) as an intracellular target of the PPIA-SFA binary complex. The formation of this ternary complex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 49 publications
1
48
0
2
Order By: Relevance
“…These findings support the notion that the CBS domain plays a key role in mediating cytoophidium assembly. A natural product sanglifehrin A (SFA), has been shown to form a complex with protein cyclophilin A (PPIA) inside human cells [ 50 ]. The PPIA-SFA complex is able to bind with IMPDH2, but not IMPDH1, at the CBS domain and thereby suppress proliferation of lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
“…These findings support the notion that the CBS domain plays a key role in mediating cytoophidium assembly. A natural product sanglifehrin A (SFA), has been shown to form a complex with protein cyclophilin A (PPIA) inside human cells [ 50 ]. The PPIA-SFA complex is able to bind with IMPDH2, but not IMPDH1, at the CBS domain and thereby suppress proliferation of lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
“…IMPDH2 is believed to be a fascinating target for cancer therapy due to its overexpression particularly in rapidly proliferating and neoplastic cells. A growing number of studies have demonstrated that IMPDH2 was closely implicated in cellular proliferation and tumorigenesis [ 4 , 26 28 ]. Herein, we found that IMPDH2 was upregulated at the mRNA and protein level in CRC cell lines, in agreement with a previous study [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, the preclinical molecule Sanglifehrin A (Table 1b) is known to act as a molecular glue linking IMPDH with cyclophilin A (Fig. 5b) 73 , which itself is implicated in viral capsid packaging, even though it itself is not a human "prey" in the viral-human protein interactome. Similarly, direct viral-human interactions with proteins regulated by the mTORC1 pathway, such as LARP1, and FKBP7, which interact with the viral N and Orf8 proteins, led us to inhibitors of mTORC1, even though that kinase itself is not found to directly interact with a viral protein ( Fig.…”
Section: Identification Of Existing Drugs Targeting Sars-cov-2 Human mentioning
confidence: 99%